UKM "SOLAKIS HARJO" "SOUVENIR GELAS LUKIS KHAS SIDOARJO" (Glasspainting) - Tirtoni, Feri; Astuti, Cindy Cahyaning (Jurnal Abadimas Adi Buana, 2017)
In the plan of the implementation of community service activities entitled "Making Souvenir Products of Typical Painting Sidoarjo" the purpose set is through this activity will create a group of UKM Souvenir Gelas Painting Typical Sidoarjo In Sukodono Village, which will be spearheaded youth of youth from Partners 1 / Karang Taruna Group RT 05 RW 02 Desa Jumput Rejo Sukodono and Partners 2 / Karang Taruna Group RT 02 RW 01 Desa Jumput Rejo Sukodono which will firstly perform an improvement of the quality of human resources in youth group of youth at Partner 1 and Partner 2 so that they have skill production of terrarium souvenir as well as having the ability of management and marketing strategy of the product so that it can become independent entrepreneur candidate and can make the product as one of the local superior product of the kecamatan Taman especially. And the solution offered is by providing increased in Partners 1 and Partner 2 through several methods as follows : Method of socialization activities "approach and the provision of knowledge of the business prospects of production Souvenir Gelas Lukis Khas Sidoarjo, Method of workshop and training of production Souvenir Gelas Lukis Khas Sidoarjo, Method of workshop and management training marketing strategy of Souvenir Gelas Lukis Khas Sidoarjo, Method of controlling and developing UKM product Souvenir Gelas Lukis Khas Sidoarjo, Evaluation and program of quality control of UKM product Souvenir Gelas Lukis Khas Sidoarjo. It is expected that through this production skill training can increase the community's independence through local income to contribute to achieve community self-sufficiency through training and production skills Souvenir Gelas Lukis Khas Sidoarjo products to improve the local economy, especially karang taruna warga Desa Jumput Rejo residents who previously only status as students and students only and can open the opportunity to become a Prospective Entrepreneur reliable. Keywords : UKM, Souvenir Gelas Lukis Khas Sidoarjo, Glass Painting